Aquatic macroinvertebrate abundance in French experimental polyculture fishponds - Marie Maillot; Marc Roucaute; Christophe Jaeger; Joël Aubin (Ecological Solutions and Evidence, 2023)
Abstract Ponds host a variety of invertebrate species and contribute greatly to global biodiversity. Aquaculture influences macroinvertebrate diversity and productivity in ponds through several practices, such as macrophyte and water management. Fish stocking is also considered controversial for preserving biodiversity through the direct predation upon natural species and changes induced on the biotope. An experiment examined whether compartmentalized ponds with temporarily fish‐free areas had higher fish productivity and macroinvertebrate abundance and diversity than open ponds. The experimental design consisted of two treatments—compartmentalized (C) or open (O)—each applied to three ponds. Roach (Rutilus rutilus), tench (Tinca tinca) and common carp (Cyprinus carpio) were stocked in the ponds in March 2021. Juvenile pikeperch (Sander lucioperca) were stocked in the ponds in June. In the C ponds, three areas were created and opened successively: (C1) corresponding to ¼ of the pond surface to host roach, tench and common carp from March to May; (C2) ¼ of the pond surface restricted to fish from March to May; and (C3) ½ of the surface restricted to fish from March to July, except for juveniles of pikeperch which were stocked in June. We investigated patterns in abundance, dry biomass and productivity of macroinvertebrates four times from March to October. This article presents observed macroinvertebrate abundances and weighted dry biomass, and productivity estimated from them. Overall, 77,749 individuals were identified, of which one‐third were Chironomini and another one‐third were Oligochaeta. The invasive red swamp crayfish (Procambarus clarkii) was found in one pond in October. The two highest taxonomic richness values were found in C ponds (71 and 69 taxa). The lowest taxonomic richness (61 taxa) was in an O pond. Although dry biomass was clearly higher in the C ponds in March, no tendency could be seen between C and O ponds throughout the experiment. No difference in productivity was found between the C and O ponds among the experiment. By reporting macroinvertebrate abundance, biomass, productivity, size classes, developmental stages and high‐resolution taxonomic identification in a freshwater polyculture system, this dataset is one of the first of its kind.